Validation of the Arab Mental Health Continuum Short Form (AMHC-SF) in Oman: Psychometric properties and factorial structure - Sharif Alsoudi; Amina Benkouider; Huda Al-Manjiya (PLoS ONE, 2026)
Background The Mental Health Continuum–Short Form (MHC–SF) is a widely used instrument designed to assess three dimensions of positive mental health: emotional, social, and psychological well-being. However, there is limited evidence regarding its validity within Arab populations. Method This study aimed to validate the Arabic version of the MHC–SF (AMHC–SF) among a community-based sample in Oman. A total of 1,101 participants aged 18–65 years (M = 31.49, SD = 9.69) completed the questionnaire through an online survey. Confirmatory factor analyses (CFA) were performed to examine factorial validity, while internal consistency reliability was assessed using Cronbach’s alpha and McDonald’s omega coefficients. Discriminant validity was examined through correlations with anxiety scales. Results Confirmatory factor analysis supported the superiority of the bifactor model over the original three-factor structure, demonstrating excellent model fit (CFI = 0.99, TLI = 0.98, RMSEA = 0.032) and substantial general factor loadings (0.64–0.76). Reliability estimates for the total scale and subscales were excellent, with Cronbach’s alpha and McDonald’s omega coefficients ranging from 0.86 to 0.95. The AMHC-SF also showed apparent discriminant validity, as higher well-being scores were associated with lower anxiety levels. Conclusion The findings support the factorial validity, reliability, and discriminant validity of the AMHC–SF, confirming its cross-cultural applicability within the Arab context. The scale represents a brief, psychometrically sound instrument for assessing positive mental health among adults in Oman and other Arabic-speaking populations.